1999
DOI: 10.3109/10976649909088337
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Myocardial Infarction After Coronary Reperfusion Detected In Vivo by Magnetic Resonance Imaging in Humans: Prevalence and Clinical Implications

Abstract: With the advent of thrombolytic therapy, hemorrhagic myocardial infarction (HMI) has been observed in experimental and human autopsy studies. However, its clinical implications remain undetermined, because of the absence of a reliable method to detect its presence in vivo. This study was designed to evaluate the clinical implications of HMI detected by magnetic resonance (MR) imaging in vivo after coronary reperfusion. Thirty-nine patients with acute myocardial infarction (AMI) were studied. Percutaneous trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 23 publications
3
49
0
2
Order By: Relevance
“…Furthermore, the combination of T 2 -weighted and contrast-enhanced T 1 -weighted sequences were used to detect and discriminate acute from chronic infarct (54) and intramyocardial hemorrhage from MO in patients (Fig. 5) (55). MR imaging with late gadolinium enhancement technique is the gold standard technique for determining the location and extent of myocardial necrosis including no-reflow zone (56).…”
Section: Cellular Injury Gadolinium Imagingmentioning
confidence: 99%
“…Furthermore, the combination of T 2 -weighted and contrast-enhanced T 1 -weighted sequences were used to detect and discriminate acute from chronic infarct (54) and intramyocardial hemorrhage from MO in patients (Fig. 5) (55). MR imaging with late gadolinium enhancement technique is the gold standard technique for determining the location and extent of myocardial necrosis including no-reflow zone (56).…”
Section: Cellular Injury Gadolinium Imagingmentioning
confidence: 99%
“…Both T2*-weighted and T2-weighted CMR techniques have been used to detect acute reperfusion intramyocardial hemorrhage. [31][32][33][34][35][36]38,39,43 After intramyocardial hemorrhage, oxyhemoglobin in the RBCs extravasated into the myocardial interstitium is slowly converted into paramagnetic forms, such as deoxyhemoglobin and methemoglobin, in the acute phase of myocardial infarction. 1 Our current study has shown that, in the chronic phase of infarction (ie, months after infarction), iron from the extravasated RBCs is externalized and crystallized to form the highly paramagnetic hemosiderin deposits.…”
Section: Detection Of Regional Iron Deposition After Hemorrhagic Infamentioning
confidence: 99%
“…Cine steady-state free precession 37 2 ), T2*-weighted 38,39 (TR=240 milliseconds; 6 TEs=2.6 milliseconds−13.7 milliseconds with ΔTE=2.2 milliseconds, flip angle=10°; BW=355 Hz/pixel; in-plane resolution=1.6×1.6 mm 2 ), and late gadolinium enhancement 40 (LGE; inversion-recovery prepared fast low-angle shot; TR =1 R-R interval; TE=3.32 milliseconds; BW=235 Hz/pixel, 1.6×1.6 mm 2 ) images of contiguous short-axis sections of the LV along with 2-, 3-, and 4-chamber long-axis views of the heart were acquired. Commonly used imaging parameters were slice thickness of 10 mm and number of averages of 1.…”
Section: Patient Selection and Cmr Imaging Studiesmentioning
confidence: 99%
“…Cardiac magnetic resonance (MR) imaging based on either T2*-weighted (16,18,(21)(22)(23)(24) or T2-weighted (15,17, Implication for Patient Care n The occurrence of myocardial reperfusion hemorrhage, which has been associated with acute myocardial damage and adverse chronic remodeling, is expected to be more reliably assessed with T2* cardiac MR imaging than with T2-based cardiac MR imaging.…”
Section: Patient Studiesmentioning
confidence: 99%